Nucleotide Sequences of Coat Protein Genes for Three Isolates of Barley Yellow Dwarf Virus and their Relationships to Other Luteovirus Coat Protein Sequences - Vincent, J. R.; Ueng, P. P.; Lister, R. M.; Larkins, B. A. (Journal of General Virology, 1990)
Barley yellow dwarf virus (BYDV) can be separated into two groups based on, among other criteria, serological relationships that are presumably governed by the viral capsid structure. Nucleotide sequences for the coding regions of coat proteins of approximately 22 K were identified for the MAV-PS1, P-PAV (group 1) and NY-RPV (group 2) isolates of BYDV. The MAV-PS1 and P-PAV coat protein sequences shared 71 % deduced amino acid similarity whereas that of the NY-RPV isolate shared no more than 51 % similarity with either the MAV-PS1 or the P-PAV sequence. Other comparisons showed that these and other BYDV coat protein sequences examined to date share a high degree of identity with those identified from other luteoviruses. Among luteovirus coat protein sequences in general, several highly conserved domains were identified whereas other domains differentiate MAV- PS1 and PAV isolates from NY-RPV and other luteoviruses. Sequence similarities and differences among BYDV coat proteins (approx. 22K) are consistent with the serological relationships exhibited by these viruses. Amino acid sequence comparisons between BYDV isolates that share common aphid vectors indicate that it is unlikely that these coat proteins are involved in aphid specificity.